2022
DOI: 10.3389/fimmu.2022.829525
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Bile Acids in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic immune-mediated inflammatory disorder of the gastrointestinal tract that arises due to complex interactions between host genetic risk factors, environmental factors, and a dysbiotic gut microbiota. Although metagenomic approaches have attempted to characterise the dysbiosis occurring in IBD, the precise mechanistic pathways interlinking the gut microbiota and the intestinal mucosa are still yet to be unravelled. To deconvolute these complex interactions, a more red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 127 publications
0
42
0
Order By: Relevance
“…Here we focused on the dataset PRISM + NLIBD because gut microbiomes of human adults have been investigated more extensively. For this purpose, we focused on the bile acid metabolism which is relatively well-studied [50, 51, 52, 53, 54] and is shown to be associated with human gastrointestinal diseases such as gastrointestinal cancers [53] and IBD [55, 56]. We carefully chose metabolites that are related to the primary, conjugated, and secondary forms of cholate and chenodeoxycholate.…”
Section: Resultsmentioning
confidence: 99%
“…Here we focused on the dataset PRISM + NLIBD because gut microbiomes of human adults have been investigated more extensively. For this purpose, we focused on the bile acid metabolism which is relatively well-studied [50, 51, 52, 53, 54] and is shown to be associated with human gastrointestinal diseases such as gastrointestinal cancers [53] and IBD [55, 56]. We carefully chose metabolites that are related to the primary, conjugated, and secondary forms of cholate and chenodeoxycholate.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we demonstrated that two BAs DCA and TCA induce different Ca 2+ signals and have distinct properties for BA-induced cell permeabilization. Our results suggest that at lower concentrations DCA may act as a signaling molecule on vagal NG neurons, however, at higher concentrations, it can lead to cell death, which may contribute to pathological changes in several inflammatory bowel diseases [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these characteristic alterations of BAs are considered to correlate with the disease severity of IBD ( Duboc et al, 2013 ; Kriaa et al, 2022 ). Recent studies have also provided evidence for the involvement of BAs in IBD-associated autophagy, apoptosis, and inflammasome pathways ( Thomas et al, 2022 ). Meanwhile, the interactions of BAs with intestinal epithelial cells and immune cells have also been revealed, further providing novel insights into the gut microbiota-BA-host axis in the pathogenesis of IBD ( Yang et al, 2021 ; Kriaa et al, 2022 ).…”
Section: High Correlation Between Dysbiosis Of Gut Microbiota and Ibdmentioning
confidence: 99%